Students' Mathematical Construction Process in Solving Geometry Problems on Minimum Competency Assessment Questions - Henry Suryo Bintoro; Y.L. Sukestiyarno; Mulyono Mulyono; Walid Walid (Universitas Negeri Semarang, 2021)
The purpose of this study was to describe the students' mathematical construction process in solving geometry problems on MCA questions based on APOS theory. This research is a type of exploratory descriptive qualitative research conducted at SMK PGRI 1 Kudus in the academic year 2021/2022. The research subjects were 30 students of class XI. The research instrument used is interview guide, documentation, and numeracy literacy test questions. APOS theory is used to analyze the construction process of students in solving geometry problems in numeracy literacy questions. The data analysis technique used is data reduction, data presentation, and conclusion drawing data. The results showed that at the action stage, the subject was able to correctly identify numeracy literacy problems. Furthermore, in the process stage, the subject can find a relationship between known problems and concepts that have been understood previously. This is done by recalling trigonometric formulas and comparison formulas. At the object stage, the subject can determine the height of the gazebo and the area of ​​the gazebo correctly. At the schema stage, the subject can generalize that the height and area of ​​the gazebo roof can be found by drawing a gazebo sketch to facilitate the completion process. The subject uses the concept of trigonometric formulas and comparative formulas to find the solution. Subjects can find answers correctly and completely in solving geometry problems on MCA questions.